دراسة البروتوكول OpenFlow والمتحكم POX في الشبكات المعرفة بالبرمجة SDN باستخدام Mininet - Ahmad, Ahmad Saker; Mohammad, Afraa (Latakia University Journal -Engineering Sciences Series, 2019)
دراسة البروتوكول OpenFlow والمتحكم POX في الشبكات المعرفة بالبرمجة SDN باستخدام Mininet أحمد صقر أحمد عفراء محمد على الرغم من التطور الهائل في مجال تقانة المعلومات، وظهور آليات مختلفة لتحسين الأداء العام للشبكة، إلا أنها لم تتناول تطوير البنية التحتية للشبكة، مما دفع الباحثين إلى إيجاد تقنية بهدف تطوير معمارية الشبكة ونتج عن ذلك ظهور الشبكات المعرفة بالبرمجةSoftware Defined Networks (SDN)) ) التي تعتبر نقلة نوعية في مجال الشبكات، لما قدمته من مزايا في تحسين الأداء وإمكانية التطوير اللامحدود. تعتبر SDN الجيل القادم للبنية التحتية في عالم الشبكات، لكونها تستطيع إنجاز ما لا يمكن أن تقدمه الشبكات التقليدية التي تحتوي على مبدل أو موجه مسؤول عن اتخاذ قرارات التوجيه وتنفيذ هذه القرارات، بينما قدمت SDN فصلاً بين اتخاذ قرارات التوجيه(Control Plane) وتنفيذ هذه القرارات(Data Plane) ، ويعتبر هذا الفصل هو التطور الكبير الذي قدمته الشبكات المعرفة بالبرمجة. يتم تنظيم التواصل بين الأجهزة الموجودة في الـData Plane) ) والمتحكم ((Controller، الذي يعتبر العنصر الأكثر أهميةً، ويمثل عقل الشبكة من خلال بروتوكول التدفق المفتوح (OpenFlow Protocol) الأكثر شهرةً في تقنية SDN. يقدم هذا البحث دراسة البروتوكول OpenFlow والتعرف على آلية الاتصال بين المبدل والمتحكم وماهي الرسائل المتبادلة بينهما، إضافةً إلى دراسة المتحكم POX الذي يعد من المتحكمات الهامة والشهيرة في SDN وكيف يحقق ذكاء الشبكة وإمكانية برمجته لينفذ أكثر من تطبيق مما يحقق مفهوم SDN ، ومن ثم قياس إنتاجية وتأخير هذا المتحكم، وبالتالي تتشكل لدينا معرفة كاملة حول مكونات تقنية SDN مما يساعدنا في اقتراح وتنفيذ عدة تطبيقات مختلفة. In spite of the tremendous development in the field of information technology and the emergence of different mechanisms to improve the overall performance of the network, it did not study the development of the network infrastructure, prompting researchers to find a technology to develop the network architecture and the result was emergence of Software Defined Networks (SDN) which is a quantum leap in networking for its advantages in improving network performance and scalability. SDN is the next generation of infrastructure in the world of networks, because it can accomplish what can’t be done by traditional networks which contain a switch or a router responsible for making decisions and implementing these decisions, while SDN provided a split between the decision making (Control Plane) and (Data Plane), and this division is the great development provided by Software Defined Networks. Communication between devices in the Data Plane and controller which is the most important element and represents the brain of network is driven through OpenFlow protocol which is the most popular protocol in SDN This research provides a study of OpenFlow protocol, the mechanism of communication between switch and the controller and what are the exchanged messages. In addition to study of POX controller that is one of important and famous controllers in SDN and how to achieve the intelligence of the network and the possibility of programming to implement many applications in order to realize the concept of SDN, then we measured throughput and latency of this controller, and thus we have a full knowledge of the components of SDN technology which helps us to propose and implement many different applications.